Perjanjian Internasional Sebagai Sumber Hukum Internasional Dalam Praktik Hubungan Antar Negara - Pentana Seniwati; Mutiara Deja Saputri; Nabila Zahra Okta Dwiwani; Ema Septaria; M. Ilham Adepio (GLOBAL SCIENTS PUBLISHER, 2026)
International agreements are one of the sources of international law that have an important role in regulating relations between countries in the international community. International treaties not only serve as a binding legal basis for the countries to which they are parties, but also serve as an instrument to create legal certainty, stability, and international cooperation. This study aims to analyze the position of international agreements as a source of international law, the process of their formation, their binding force, and their implementation in the practice of relations between countries. The research method used is a qualitative approach with library research, reviewing literature in the form of books, scientific journals, international legal documents, and the 1969 Vienna Convention on the Law of Treaties. The results of the study show that international treaties have a strategic position in the international legal system as stipulated in Article 38 of the Statute of the International Court. The establishment of international agreements is carried out through the stages of negotiation, signing, ratification, and enactment, which ensure the legitimacy and approval of the parties to the agreement. The binding power of international treaties is based on the principle of pacta sunt servanda, which affirms that every agreement must be implemented in good faith by the parties. The implementation of international agreements in the practice of relations between countries is influenced by national legal systems, political commitments, institutional capacity, and economic and social dynamics. This research confirms that international agreements play a key role as a key instrument in maintaining state compliance, preventing conflicts, and facilitating sustainable global cooperation. Therefore, international treaties have not only formal legal val.